Maternal history of child maltreatment and household chaos: examining the mediating role of maternal and child psychopathology - Andrews, Krysta (Child maltreatment, 2023)
Caregiver history of childhood maltreatment can have pervasive effects on familial and household dynamics. Maternal history of child maltreatment (MCM) is linked to maternal depressive symptoms and offspring behavioural problems. Further, maternal and child mental health are associated with chaotic home environments. In this study, we examined the potential mediating roles of maternal depressive symptoms and child behavioural problems in the association between MCM and household chaos. A sample of 133 mother?child dyads participated in home visits during which mothers completed questionnaires measuring their history of child maltreatment, depressive symptoms, household chaos and child behaviour problems. Mothers also conducted videotaped home tours related to household chaos. Structural equation modelling results indicated that MCM was indirectly associated with higher household chaos via elevated maternal depressive symptoms and child externalizing, but not internalizing behaviour problems. Interventions aimed at mitigating the effects of MCM on maternal and child psychopathology may positively influence household dynamics.